2021
DOI: 10.15566/cjgh.v8i2.579
|View full text |Cite
|
Sign up to set email alerts
|

Religion as a protective factor against adolescent smoking habits: evidence from Spain

Abstract: Background: There are a wide number of assessments suggesting that being a member of a religious community inhibits adolescents’ risky behaviours and, consequently, can act as a protective factor against the consumption of smoking substances. Methods: We have analysed a structured questionnaire answered by 1935 adolescents from Tarragona (Spain). Results: We have found that variables linked to family were the principal explanatory factors of adolescents’ smoking habits. Living with two parents was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The fact that being male is a significant risk factor of cannabis use is in accordance with mainstream findings in literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The significant and negative relation of MONITOR with USE is widely supported by literature [4,5,[9][10][11][19][20][21][22][23], that found similar results for the influence of parental monitoring on drug consumption. Analogous conclusion it is extracted from OLR finding on the impact of RELIGION over USE and reviewed literature [4,5,7,8,10,11,15,16,20,21,24,25,29,[31][32][33].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The fact that being male is a significant risk factor of cannabis use is in accordance with mainstream findings in literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The significant and negative relation of MONITOR with USE is widely supported by literature [4,5,[9][10][11][19][20][21][22][23], that found similar results for the influence of parental monitoring on drug consumption. Analogous conclusion it is extracted from OLR finding on the impact of RELIGION over USE and reviewed literature [4,5,7,8,10,11,15,16,20,21,24,25,29,[31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…Nasim et al [32] reported that religion has a dissuasive effect on the risk behaviors of adolescents, interfering with their use of drugs by helping them to internalize messages that discourage consumption. The significant protective effect of religiosity in cannabis smoking has been reported in samples from diverse cultures [4,5,7,8,10,11,15,16,20,21,24,25,29,[31][32][33].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the latter assertion depends on the culture of the society being analysed; the more similar the gender roles are, the fewer differences in substance use tend to be ( McHugh et al, 2018 ). In some cases, women may even consume more tobacco than males, as shown in studies by Eisenberg et al (2014) and Andres-Sanchez, Belzunegui-Eraso & Fernández-Aliseda (2021) . On the other hand, men may have greater engagement with cannabis ( Francis et al, 2019 ; Andres-Sanchez & Belzunegui-Eraso, 2022 ), tend more toward polydrug use ( Brière et al, 2011 ) and are more likely to develop disorders associated with such practices ( McHugh et al, 2018 ).…”
Section: Discussionmentioning
confidence: 97%